Landscape, National Identity and the Medieval Past in England, c.1840–1914. (8th October 2022) - Readman, Paul
Abstract: This article re-examines the place of the Middle Ages in nineteenth- and early twentieth-century English culture. In doing so, it presents an argument about the interrelationship of landscape, history and English national identity. Emphasising the importance of the medieval past to mainstream constructions of Englishness, the article shows how this importance largely derived from the felt presence of the Middle Ages in the physical environment, in the landscape of England. Their history congealed in the fields, forests, hills, towns and villages of the present day, the Middle Ages were readily accessible through imaginative agency and possessed of vital contemporary meaning. Embodied experience of landscape offered Victorians and Edwardians compelling evidence of the long continuities of English national history, from Anglo-Saxon times onwards. In an increasingly democratic context, the medieval presence in the landscape was evidence of the continuity not only of the institutions of the realm, but of the English people themselves. Until at least the First World War, and perhaps beyond, the tangible heritage of the Middle Ages in the English landscape served as an important source of reassurance of the nation's endurance and progress, amid the transformations of modernity.